Identifikasi Tingkat Resiko Kekumuhan di Kawasan Lempenge Kabupaten Lombok Utara - Pratama, Indah Arry (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
Based on Undang Undang no 1 tahun 2011, The implementation of residential areas is carried out with the aim of realizing an area that functions as a residential environment and a place for activities that support a planned, comprehensive, integrated and sustainable life and livelihood in accordance with the spatial plan. Regional development is strongly influenced by the rate of population. With the increasing population growth, the demand for land in the region also increase. As developing area, Lombok Utara Regency will face problems that are commonly encountered by urban areas,as was the case in Lempenge areas. The research was conducted by risk identification on the delination of areas that have potential to become slums or become slums. Based on the results of the identification of the potential risk of slums settlement in Lempenge Areas is a middle slums level with priority handling construction and improvement of sewerage channels, road, and drainage systems.